Synthesis of embedded Au nanostructures by ion irradiation: influence of ion induced viscous flow and sputtering - Singh, Udai B.; Agarwal, D. C.; Khan, S. A.; Mohapatra, S.; Amekura, H.; Datta, D. P.; Kumar, Ajay; Choudhury, R. K.; Chan, T. K.; Osipowicz, Thomas; Avasthi, D. K. (Beilstein Journal of Nanotechnology, 2014)
The ion-irradiation induced synthesis of embedded Au nanoparticles (NPs) into glass from islands of Au on a glass substrate is studied in the context of recoiling atoms, sputtering and viscous flow. Cross sectional transmission electron microscopy studies revealed the formation of Au NPs embedded in the glass substrates by the 50 keV Si− ion irradiation of irregularly shaped Au nanostructures on the glass surfaces at a fluence of 3 × 1016 ions/cm2. The depth profiles of Au in the samples were obtained from high-resolution Rutherford backscattering spectrometry studies. The results from TRIDYN simulation reveal the role of various ion-induced processes during the synthesis of the embedded Au NPs, viz. sputtering and recoiling atoms. Simulation and experimental results suggest that the viscous flow is one of the major factors that are responsible for the embedding of Au nanoparticles into the glass substrate.
Keywords: embedded nanoparticles; ion beam irradiation; recoil implantation

(untitled) - Elghanian, R.; Storhoff, J. J.; Mucic, R. C.; Letsinger, R. L.; Mirkin, C. A. (Science, 1997)

(untitled) - Maier, S. A.; Kik, P. G.; Atwater, H. A.; Meltzer, S.; Harel, E.; Koel, B. E.; Requicha, A. A. G. (Nat. Mater., 2003)

(untitled) - Mock, J. J.; Smith, D. R.; Schultz, S. (Nano Lett., 2003)

(untitled) - Ozbay, E. (Science, 2006)

(untitled) - Vasseur, J. O.; Akjouj, A.; Dobrzynski, L.; Djafari-Rouhani, B.; El Boudouti, E. H. (Surf. Sci. Rep., 2004)

(untitled) - Khan, S. A.; Avasthi, D. K.; Agarwal, D. C.; Singh, U. B.; Kabiraj, D. (Nanotechnology, 2011)

(untitled) - Kumar, T.; Khan, S. A.; Singh, U. B.; Verma, S.; Kanjilal, D. (Appl. Surf. Sci., 2012)

(untitled) - Singh, U. B.; Agarwal, D. C.; Khan, S. A.; Kumar, M.; Tripathi, A.; Singhal, R.; Panigrahi, B. K.; Avasthi, D. K. (Appl. Surf. Sci., 2011)

(untitled) - Singh, U. B.; Agarwal, D. C.; Khan, S. A.; Mohapatra, S.; Tripathi, A.; Avasthi, D. K. (J. Phys. D: Appl. Phys., 2012)

(untitled) - Singh, U. B.; Agarwal, D. C.; Khan, S. A.; Tripathi, A.; Kumar, A.; Choudhury, R. K.; Panigrahi, B. K.; Avasthi, D. K. (Radiat. Eff. Defects Solids, 2011)

(untitled) - Khan, S. A.; Srivastava, S. K.; Avasthi, D. K. (J. Phys. D: Appl. Phys., 2012)

(untitled) - Avasthi, D. K.; Mishra, Y. K.; Singh, F.; Stoquert, J. P. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2010)

(untitled) - Khan, S. A.; Heinig, K.-H.; Avasthi, D. K. (J. Appl. Phys., 2011)

(untitled) - Mishra, Y. K.; Avasthi, D. K.; Kulriya, P. K.; Singh, F.; Kabiraj, D.; Tripathi, A.; Pivin, J. C.; Bayer, I. S.; Biswas, A. (Appl. Phys. Lett., 2007)

(untitled) - Mishra, Y. K.; Singh, F.; Avasthi, D. K.; Pivin, J. C.; Malinovska, D.; Pippel, E. (Appl. Phys. Lett., 2007)

(untitled) - Mishra, Y. K.; Kabiraj, D.; Avasthi, D. K.; Pivin, J. C. (Radiat. Eff. Defects Solids, 2007)

(untitled) - Perkins, J. G.; Stroud, P. T. (Nucl. Instrum. Methods, 1972)

(untitled) - Grötzschel, R.; Klabes, R.; Kreissig, U.; Schmidt, A. (Radiat. Eff. Defects Solids, 1978)

(untitled) - Bruel, M.; Floccari, M.; Gailliard, J. P. (Nucl. Instrum. Methods, 1981)

(untitled) - Möller, W.; Eckstein, W.; Biersack, J. P. (Comput. Phys. Commun., 1988)

(untitled) - Möller, W.; Eckstein, W. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1984)

(untitled) - Stepanov, A. L.; Hole, D. E.; Townsend, P. D. (J. Non-Cryst. Solids, 1999)

(untitled) - Hu, X.; Cahill, D. G.; Averback, R. S. (J. Appl. Phys., 2002)

(untitled) - Klimmer, A.; Ziemann, P.; Biskupek, J.; Kaiser, U.; Flesch, M. (Phys. Rev. B, 2009)

(untitled) - Osipowicz, T.; Seng, H. L.; Chan, T. K.; Ho, B. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2006)

(untitled) - Sigmund, P. (Phys. Rev., 1969)

(untitled) - Ziegler, J. F.; Ziegler, M. D.; Biersack, J. P. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2010)

(untitled) - Bolse, W. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1993)

(untitled) - Prakash, J.; Tripathi, A.; Rigato, V.; Pivin, J. C.; Tripathi, J.; Chae, K. H.; Gautam, S.; Kumar, P.; Asokan, K.; Avasthi, D. K. (J. Phys. D: Appl. Phys., 2011)